Does Androgen Hormone Influences Sexual Orientation? - Nasihun, Taufiqurrahman (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2015)
Now days lesbian, gay, bisexual, and transgender are abbreviated as LGBT is the most popular word and being sensible in the world, especially in Indonesia. Based on human right principles, any person in the world including in Indonesia is free to express their gender identity and sexual orientation, even the same sex marriage, freely from unlawful discrimination and violations (Office of Personnel Management, 2015; Yogyakarta Principles, 2006). However, because of the culture and religion differences backgrounds, Indonesians have given this issue various responses. In general, Indonesian public opinion on LGBT are split into two different groups, one minority group is proponent to present of LGBT and any things related to it, and another majority groups are opponent. Objective of this editorial is to discuss how sexual orientation develop from prenatal until emerging of clinical manifestation in adulthood, by no mean to support either group. Otherwise, to give more insight about how male and female get their appropriate sexual orientations and why some of them get inappropriate sexual orientations.